PENINGKATAN STIMULASI MOTORIK KASAR ANAK BERKEBUTUHAN KHUSUS MELALUI SENAM CERIA DI PPDK CHANGLUN, KAMPUNG TRADISI, MALAYSIA. - Gustian, Ratu Mayla; Handayani, Sri Lestari; Setyaningsih, Maryanti; Amirullah, Gufron (Damhil: Jurnal Pengabdian kepada Masyarakat, 2024)
The cheerful gymnastics activity held at PPDK Changlun, Traditional Village, is a program designed to improve the gross motor skills of children with special needs. Through a series of fun and easy-to-follow movements, this program aims to help children develop body coordination, balance and muscle strength. This cheerful exercise is carried out with a positive and inclusive approach, accommodating the special needs of each child. A cheerful and enthusiastic atmosphere makes children feel comfortable and motivated to participate actively. The results show high enthusiasm from the children, which can be seen from their enthusiasm in following every movement and their enthusiasm for interacting with their friends. This program has proven effective in motivating children to move, learn and build self-confidence. Cheerful gymnastics at PPDK Changlun is a fun place for children with special needs to develop their motor skills, improve physical and mental well-being, and build positive social relationships. It is hoped that this program can become an example for similar programs in other places, and will continue to be developed to achieve more optimal results.